HUBUNGAN IKLIM (CURAH HUJAN, SUHU UDARA, KELEMBABAN UDARA DAN KECEPATAN ANGIN) DENGAN KEJADIAN DIARE DI KOTA JAKARTA PUSAT PADA PERIODE TAHUN 2004-2013 - lidia oktavia; taufik ashar; surya dharma (Lingkungan dan Kesehatan Kerja, 2015)
ABSTRACT Diarrhea was a public health problem in developing country like Indonesia. Jakarta Pusat was endemic diarrhea area. Climate was proponent factors of diarrhoea occurrence. Research sites in Jakarta Pusat was done by collecting data recorded from the years 2002-2013 from Department of Health in Jakarta Pusat and Central Bureau of Statistics in DKI Jakarta Province. The design of this research was time trend ecological study which the unit of analysis is per month and per year during ten years. This research aims to know the relationship among rainfall, temperature, humidity and wind’s speed with the diarrhea occurrence from the years of 2004-2013 in Jakarta Pusat. Data analysis was performed by using univariate and bivariate analysis using pearson correlation and simple linear regression. The results of this research, there was significant correlations of rainfall with diarrhea case per month (p = 0,031) and strong correlations (r = 0,621), had positive pattern, there was significant correlations of humidity with diarrhea (p = 0,006) and strong correlations (r = 0,739), had positive pattern, while temperature per month and wind’s speed per month did not correlate significantly. There was significant correlation of Wind’s speed with diarrhea per year (p = 0,025), and strong correlations (r = 0,697), had positive pattern. Based on the research results, it was concluded that the rainfall and humidity correlated significantly with diarrhea cases per month. While the wind’s speed correlated significantly with diarrhea cases per year. Need the existence of cooperation program among Department of Health in Jakarta Pusat, relevant agencies, and society in exploiting climate variation data to prevent of diarrhea case explosion (KLB) in the future. The people always be alerted diarrhea with taking care of personal hygiene and environment